The Effect of Implementing Good Manufacturing Practices and Having a Halal Certificate on Competitiveness and Marketing Performance - Muttaqin, Firman; Huda, Nuril (Universitas Pamulang, 2025)
The implementation of Good Manufacturing Practices (GMP) or good processing of processed food adopts the food safety system from ISO 22000 which has fourteen aspects and Halal Certificate which has eleven aspects for Small and Medium Industries (SMEs) in South Kalimantan. The implementation is considered to be still mentoring because there are still inconsistencies in several aspects and is a complex process, in addition, this implementation requires other resources such as costs, time and energy. This implementation is also linked to its impact on competitiveness in this case the competitiveness of the Porter model and marketing performance. The purpose of this study is to identify the variables of GMP implementation and Halal Certification on competitiveness and marketing performance and to analyze the effect of the implementation. This research method uses Partial Least Square-Structural Equation Modeling (SEM-PLS) analysis of the results of 256 respondents from thirteen regencies/cities in South Kalimantan through purposive sampling. The research instrument is a questionnaire with a Likert scale that has been tested for validity and reliability. The results of this study found that GMP implementation has an effect on halal certification, and halal certification also has an effect on competitiveness and marketing performance. This research focuses on GMP because there are still aspects that are invalid or not implemented in food SMEs, which are actually mandatory. The implications are improving human resource skills among SMEs and encouraging the government to support food SME policies to advance.